Magnetic moments of odd-A Sb isotopes to Sb-133: Significant evidence for mesonic exchange current contributions and on core collective g factors - Stone, N; Doran, D; Lindroos, M; Rikovska, J; Veskovic, M; White, G; Williams, A; Fogelberg, B; Jacobsson, L; Towner, I; Heyde, K (1997)
The magnetic moments of (double magic + 1 proton) nuclei having a "jack-knife" j = l - s configuration form crucial tests for the theoretical treatment of mesonic exchange currents and core polarization effects in finite nuclei. The reported precision measurement and analysis of the magnetic moment of 133Sb ( 132Sn + one g 7/2 proton) μ = 3.00(1) μN provides the first such test in medium-heavy nuclei. In addition, new data on the N dependence of the 7/2 +123-133Sb ground state moments are presented. Analysis in terms of particle-core coupling indicates slightly negative collective g factors of heavy Sn core nuclei.